Dual-Enzyme Crosslinking and Post-polymerization for Printing of Polysaccharide-Polymer Hydrogel - Shen, Saiji; Shen, Jiayin; Shen, Hongdou; Wu, Chu; Chen, Ping; Wang, Qigang (Frontiers in Chemistry, 2020)
Polymer hydrogels are ideal bioprinting scaffolds for cell-loading and tissue engineering due to their extracellular-matrix-like structure. However, polymer hydrogels that are easily printed tend to have poor strength and fragile properties. The gradually polymerized reinforcement after hydrogel printing is a good method to solve the contradiction between conveniently printed and high mechanical strength requirement. Here, a new succinct approach has been developed to fabricate the printable composite hydrogels with tunable strength. We employed the HRP@GOx dual enzyme system to initiate the immediate crosslinking of chondroitin sulfate grafted with tyrosine and the gradual polymerization of monomers to form the composite hydrogels. The detailed two-step gelation mechanism was confirmed by the Fluorescence spectroscopy, Electron paramagnetic resonance spectroscopy and Gel permeation chromatography, respectively. The final composite hydrogel combines the merits of enzymatic crosslinking hydrogels and polymerized hydrogels to achieve adjustable mechanical strength and facile printing performance. The dual-enzyme regulated polymer composite hydrogels are the promising bioscaffolds as organoid, implanted materials, and other biomedical applications.